Μοναξιά: Ψυχαναλυτικές προσεγγίσεις - Γαλανάκη, Ε. (Επετηρίς Φιλοσοφικής Σχολής της Φιλοσοφικής Σχολής του Πανεπιστημίου Αθηνών, 2008)
In this essay, we describe, compare and comment on various psychoanalytic approaches to loneliness. Loneliness has long been neglected by psychologists and psychiatrists, and there are very few studies on the psychoanalytic interpretation of this universal human condition. After some conceptual clarifications, the developmental origins of loneliness are discussed (on the basis of Mahler’s and Stern’s theories). Subsequently, the relation of loneliness to anxiety and narcissism is analyzed, drawing from the Freudian framework, as well as the theories of Klein, Bion, Bowlby, Zilboorg, Kohut, Kernberg, and Balint. Other facets of the pathology of loneliness are discussed, such as the loneliness of the depressed and the borderline individual (Freud, Fairbairn, Guntrip, Kernberg). Finding solace in alternative worlds (e.g., phantasies, illusions, manic defenses, obsessive acts) is a way of dealing with painful loneliness, described in this essay. The capacity to play and to live in the location of cultural experience, according to Winnicott, are evaluated as fundamental ways of making creative use of aloneness. Solitude or beneficial aloneness – a human state highly neglected by psychology (theory and research) – is psychoanalytically approached in the theories of Freud, Winnicott, Storr, and Quinodoz. Moreover, the notion of the private self (Winnicott, Bollas, Stern, Modell, Ogden) is also developed in relation to solitude. In conlusion, the role that loneliness has played in the lives of several psychoanalysts is stressed, and an attempt to delineate the many faces of loneliness is made.